La especial legitimación de capitales contemplada en la ley 8422 - Rojas Salas, Manuel (2022)
The Law Against Corruption and Illicit Enrichment contains a number of criminal types that have not been thoroughly studied, despite their impact on the legal life of the country. These include a criminal type that comprises a very particular money laundering model, which will be approached in light of its status as a special law compared to the general type.